Wacana Perbahasan Kontradiksi Hadith - Rohaizan, Baru (2008)
Mukhtalif al-Hadith is a branch of hadith methodology, discussing particularly contradictions of a hadith. Within the framework of this science, hadith scholars have come up with ways and methods to solve any type of contradiction in a hadith. A lack of clear understanding and proper interpretation could cause all sorts of confusion leading to the reiection of a genuine hadith or a misconception towards the credibility of a hadith which are a source of legislation, civilization and the Islamic way of life.